Harmonic scalpel versus conventional hemorrhoidectomy - Hazem A Megahed (Wolters Kluwer Medknow Publications, 2019)
Introduction In this study, harmonic scalpel hemorrhoidectomy was compared with the classical Milligan-Morgan hemorrhoidectomy regarding the outcome and the postoperative complication rates. Patients and methods Between June 2014 and September 2018, 40 patients aged between 30 and 60 years old underwent a hemorrhoidectomy operation in Al-Azhar University Hospital, New Damietta. The patients were randomly subdivided into two groups: group A included 20 patients who underwent the classical Milligan-Morgan hemorrhoidectomy operation, which represented the conventional method, and group B included 20 patients who underwent a hemorrhoidectomy with the use of a harmonic scalpel. The outcome and postoperative complications were compared between the two groups. Results In the harmonic scalpel group (group B), the posthemorroidectomy static pain was significantly lesser on the postoperative days 3, 7, and 14, but it was nonsignificantly lesser on the first postoperative day. Moreover, there was significant decrease in mean hospital stay in group B (1.0±0.2 days) vs. in group A (conventional method group) (1.3±0.4 days). The operative time was significantly decreased in group B (15±1.1 min) versus group A (20±2.1 min). Regarding early complications such as minor bleeding and urinary retention, they were lesser in group B, but without significance. Conclusion Harmonic scalpel hemorrhoidectomy is a less time-consuming bloodless procedure and has lesser postoperative pain and bleeding when compared with conventional hemorrhoidectomy.